Optical emulation of quantum state tomography and bell test—A novel undergraduate experiment - Eden Arbel; Noa Israel; Michal Belgorodsky; Yonathan Shafrir; Alona Maslennikov; Sara P. Gandelman; Georgi Gary Rozenman (Results in Optics)
This paper presents an innovative experiment and theoretical framework designed for senior-level undergraduate students to explore quantum state tomography and Bell inequality tests. The experiment utilizes pulsed laser light and a carefully engineered optical system to emulate quantum entanglement, enabling students to investigate foundational quantum phenomena using accessible laboratory tools. Through practical measurements and simulations, students reconstruct quantum states and analyze correlations indicative of entanglement and non-locality. The setup includes polarization analysis across multiple measurement bases and culminates in the measurement of Bell’s parameter using the CHSH test. By combining experimental emulation with computational analysis, this approach provides a compelling educational bridge between abstract quantum theory and hands-on experiments, highlighting the conceptual and practical relevance of quantum entanglement in modern physics.